2014
DOI: 10.14814/phy2.12091
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid does not enhance hypoxia-induced vasodilation in healthy older men

Abstract: In response to hypoxia, a net vasodilation occurs in the limb vasculature in young healthy humans and this is referred to as “hypoxia‐induced vasodilation”. We performed two separate experiments to determine (1) if hypoxia‐induced forearm vasodilation is impaired in older men (n = 8) compared to young men (n = 7) and (2) if acute systemic infusion of ascorbic acid would enhance hypoxia‐induced vasodilation in older men (n = 8). Heart rate, mean arterial pressure, oxygen saturation, minute ventilation, forearm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 69 publications
(166 reference statements)
1
9
0
Order By: Relevance
“…It remains possible a regulatory shift occurs with aging and less overall reliance on NO-mediated dilation. This is consistent with recent findings that showed no effect of vitamin C in enhancing peripheral blood flow in older individuals, despite blunted hypoxic vasodilation (37). It is possible that the vascular responses to hypoxia do not solely rely on an intact endothelium, as Headrick and Berne (20) have suggested that adenosine mediates relaxation by both endothelial-dependent and -independent mechanisms.…”
Section: Effect Of Vitamin C On the Cerebrovascular Regulation Of Acusupporting
confidence: 91%
“…It remains possible a regulatory shift occurs with aging and less overall reliance on NO-mediated dilation. This is consistent with recent findings that showed no effect of vitamin C in enhancing peripheral blood flow in older individuals, despite blunted hypoxic vasodilation (37). It is possible that the vascular responses to hypoxia do not solely rely on an intact endothelium, as Headrick and Berne (20) have suggested that adenosine mediates relaxation by both endothelial-dependent and -independent mechanisms.…”
Section: Effect Of Vitamin C On the Cerebrovascular Regulation Of Acusupporting
confidence: 91%
“…However, we recently found that age‐associated differences in skeletal muscle hypoxic vasodilation were not observed in the skin (Pollock et al. ), thus demonstrating a situation in which skin and muscle do not respond the same. Currently, it remains unclear if peripheral and/or central chemoreceptors participate in reflex control of the cutaneous circulation.…”
Section: Introductionmentioning
confidence: 87%
“…; Pollock et al. ), but vasoconstricts during a voluntary apnea (Katragadda et al. ; Imadojemu et al.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, positive effects of moderate hypoxia, e.g., in vasodilation, ameliorations of the lipid metabolism, hypertension, insulin resistance and glucose tolerance etc. are well established (Kayser 1992;Netzer and Breitenbach 2010;Pollock et al 2014). Moderate inhibition of the mitochondrial respiration could slow down the metabolic rate and extend life span of the short-lived laboratory animal species (Honda et al 1993;Feng et al 2001;Cheung et al 2008;Copeland et al 2009;Klok and Harrison 2009;Forgan and Forster 2010;Lee et al 2010;Hwang and Lee 2011).…”
Section: Hypoxiamentioning
confidence: 99%